Dem Göttlichen ganz nah »Muße« und Theoria in der spätantiken Philosophie und Theologie - Kirchner, Andreas (Mohr Siebeck, 2020)
What is »leisure«? What is »theory«? And how are the two connected? Andreas Kirchner explains that according to Aristotle's basic definitions of the concepts of »theoría« and »scholê«, both undergo characteristic developments in the course of history, and that the philosophy and theology of late antiquity significantly contributed to this. Plotinus' Neoplatonism thus decisively extends both concepts in their essential respects, and the emerging Christian theology, which the author examines by taking Marius Victorinus, Ambrose and, above all, Augustine as examples, then builds up its definition of »leisure« and »theory«. While based on philosophical foundations on the one hand, on the other it develops its own characteristic concepts following the personal concept of God and Christian assumptions. Andreas Kirchner shows how fundamentally the thought systems as well as the respective concept of God affect the conceptual design.